Haiti : Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility-Staff Report; Staff Press Release on the Executive Board Discussion; and Statement by the Executive Director for Haiti. (IMF Staff Country Reports; Country Report, 2006)
Based on Haiti's overall satisfactory track record and the strength of the program, IMF staff supports the authorities' request for a new three-year arrangement under the Poverty Reduction and Growth Facility (PRGF). The authorities' demonstrated political commitment and high degree of ownership will be critical to secure durable success of Haiti's economic reform strategy. Haiti's requirements are expected to remain substantial, but the already identified assistance appears adequate to close the gap over the first year of the program. The strategy should include an independent assessment of the financial condition.